The relationship between personal COVID-19 vaccination decisions and cattle vaccination practices: Evidence from a survey of South Dakota beef producers - Filip Viskupič; Russell Daly; David L. Wiltse; Michael Gonda (PLoS ONE, 2026)
Objectives Vaccination was a contentious issue during the COVID-19 pandemic, and experts warned about a possibility of a spillover effect—negative attitudes toward COVID-19 vaccines might start affecting attitudes toward other vaccines. We evaluated the correlates between beef producers’ personal vaccination decisions and cattle vaccination practices. Methods Using publicly available information from USDA payment program participants, we invited 6,238 beef producers in South Dakota to participate in an online survey. The survey was conducted in October 2024 and measured the use of established cattle vaccines, attitudes toward a cattle vaccine for Highly Pathogenic Avian Influenza (HPAI), and personal COVID-19 vaccine uptake. Multivariate logistic regression was utilized to analyze the data. Results We received responses from 339 beef producers. We found that 94% of participants regularly vaccinate their cattle with established vaccines, while 24% were likely to vaccinate their cattle for HPAI when a vaccine becomes available. Over 44% of respondents never received a COVID-19 vaccination. Regression analysis results showed no association between COVID-19 vaccine uptake and the use of established cattle vaccines (aOR: 1.45, 95% CI: 0.76–2.74) and a positive and statistically significant association with the likelihood of using HPAI vaccine in cattle (aOR: 1.78, 95% CI: 1.41–2.26). Conclusion Overall, we found partial evidence for the presence of a relationship. It is plausible that beef producers who have not received a COVID-19 vaccination might be less likely to adopt new cattle vaccines in the future.